Assessment of nicotine dependence among tobacco chewers attending dental outpatient department in a tertiary care hospital - Shekhar, Saket; Nehulkar, Prachi N.; Holambe, Vimal M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Smokeless tobacco is most common form of tobacco addiction. Nicotine dependence plays important role in tobacco addiction. In the present study we try to study sociodemographic factors, type of smokeless tobacco use and its pattern and smokeless tobacco chewers and nicotine dependence among them. Methods: A cross sectional study was conducted for six months and responses from 854 smokeless tobacco chewers were collected from dental OPD of Government Medical College and Hospital, Latur, Maharashtra. A structured questionnaire was designed and filled by face to face interview and responses were analysed. Results: Out of 854 study participants more than 50% i.e. 468 (54.80%) were in age group of 25-44 years. Illiterates compromised 27.87% of study participants. Almost one third (31.14%) of study participants started using smokeless tobacco before age of 18 years. Khaini or tobacco mixed with slaked lime is preferred type of smokeless tobacco by most of the smokeless tobacco users. Most common i.e. 51.87% of study participants consumed smokeless tobacco 5-9 times a day. Almost 50% of study participants i.e. 421 (49.30%) spent Rs 100-300 on smokeless tobacco per month. Nicotine dependence is seen in 38.20% of study participants. Conclusions: Smokeless tobacco use is prevalent before age of maturity among teenagers. Nicotine dependence is seen in almost one third of smokeless tobacco users. Determining nicotine dependence is an important step in tackling nicotine dependence.